A framework of HIFZBUDDY for facilitating Qur’anic memorization: Digital learning approach - Muhamad Rizal, Adriana Najiha; Mohd Fairuz, Nurul Sofea; Mohd Said, Nuramalia; Mohd, Siti Munirah; Ahmad Hilmi, Ahmad Bazli; Mohamad Jan, Nurhidaya (Journal of Islamic, Social, Economics and Development, 2026)
The memorisation of the Qur'an is a practice that requires discipline, consistency, and practical tools to support long-term retention. However, traditional methods often face challenges such as time constraints, a lack of personalised guidance, and limited engagement. Therefore, this study proposes a framework for HifzBuddy, a mobile application that supports Qur'anic memorisation through interactive and adaptive learning features. The project first goes for analysis and identifies various challenges that may arise within the current system. Then, developing a comprehensive framework outlining effective strategies and solutions to address these problems, ensuring more efficient and sustainable outcomes. This will involve gathering data, consulting stakeholders, and applying best practices to create a robust, adaptable structure tailored to the organisation's needs. The principal results at this stage include completing the entire application framework, encompassing key features such as personalised dashboards, murajaah tools, quizzes, progress tracking, community forums, and teacher-student modules. The findings contribute a conceptual and practical model for integrating technology with Qur'anic memorisation pedagogy, leading towards the development of a scalable digital platform for global use.